Hungry for profit : the agribusiness threat to farmers, food, and the environment (New York, 2000)
"The agribusiness/food sector is the second most profitable industry in the United States - following pharmaceuticals - with annual sales over $400 billion. Contributing to its profitability are the breathtaking strides in biotechnology coupled with the growing concentration of ownership and control by food’s largest corporations. Everything, from decisions on which foods are produced, to how they are processed, distributed, and marketed is, remarkably, dictated by a select few giants wielding enormous power. More and more farmers are forced to adopt new technologies and strategies with consequences potentially harmful to the environment, our health, and the quality of our lives. The role played by trade institutions like the World Trade Organization, serves only to make matters worse. Through it all, the paradox of capitalist agriculture persists: ever-greater numbers remain hungry and malnourished despite an increase in world food supplies and the perpetuation of food overproduction. Hungry for Profit presents a historical analysis and an incisive overview of the issues and debates surrounding the global commodification of agriculture. Contributors address the growing public concern over food safety and controversial developments in agricultural biotechnology including genetically engineered foods. Hungry for Profit also examines the extent to which our environmental, social, and economic problems are intertwined with the structure of global agriculture as it now exists."